Unraveling the Impact of Copper Ions on Mineral Surfaces During Chalcopyrite–Molybdenite Flotation Separation Using Sodium Thioglycolate - Feng Jiang; Shuai He; Jiaxing Qi; Yuanjia Luo; Honghu Tang (Applied Sciences)
The efficient separation of chalcopyrite from molybdenite is crucial for the utilization of copper–molybdenum ores and is inevitably influenced by the presence of metal ions in the pulp. However, the underlying impact mechanisms remain unclear. This study systematically investigated the influence of Cu2+ on the flotation separation of chalcopyrite and molybdenite, with sodium thioglycolate (STG) as a depressant. Flotation experiments revealed that Cu2+ in the STG system significantly reduced molybdenite recovery and hindered selective separation. Characterization using contact angle, zeta potential, and UV–Vis analysis demonstrated that the presence of Cu2+ triggered STG adsorption on the molybdenite surface, thereby increasing its hydrophilicity. XPS analysis showed that Cu2+ adsorbed onto the molybdenite surface as Cu(I), creating reactive sites for the –SH or –COO− groups in STG. This interaction forms a stable molybdenite–Cu(I)–STG complex through chemisorption, significantly suppressing molybdenite flotation. DFT calculations further demonstrated that Cu2+ enhanced the reactivity between STG and molybdenite. These findings provide a comprehensive understanding of the influences of Cu2+ on the flotation separation between chalcopyrite from molybdenite, providing valuable insights into further optimizing copper–molybdenum flotation separation processes.